New Tirucallane-Type Triterpenoids from Guarea guidonia - Hernandez, Vanessa; De Leo, Marinella; Cotugno, Roberta; Braca, Alessandra; De Tommasi, Nunziatina; Severino, Lorella (Planta Medica, 2018)
The aerial parts of Guarea guidonia afforded three new tirucallane-type triterpenoids: 3,4-seco-tirucalla-4(28),8(9),24(25)-trien-7α,11α-dihydroxy-21,23-epoxy-3,11-olide, named guareolide (1), 3,4-seco-tirucalla-4(28),7(8),24(25)-trien-21-hydroxy-21,23-epoxy-3-oic acid, named guareoic acid A (2), and 3,4-seco-tirucalla-4(28),7(8),24(25)-trien-21,23-epoxy-3-oic acid, named guareoic acid B (3), of which 1 possessed an unusual seven-membered lactone ring. Seven known terpenes were also isolated and characterized as flindissone, 7-acetyldihydronomilin, picroquassin E, boscartol C, and cneorubins A, B, and X. Their structures were determined by spectroscopic methods including one-dimensional and two-dimensional nuclear magnetic resonance analysis and high-resolution mass spectrometry. The isolates were investigated for their potential cytotoxic activity on Jurkat, HeLa, and MCF7 cancer cell lines. Flindissone and compound 2 showed an antiproliferative activity in all cell lines. Further studies revealed that flindissone, the most active compound, induced in Jurkat and HeLa cells both cytostatic and cytotoxic responses.
Keywords: Guarea guidonia; Meliaceae; tirucallane triterpenes; cytotoxicity; antiproliferative activity